Cell-Free Versus Cell-Seeded Tissue-Engineered Heart Valves: Lessons From Preclinical and Clinical Studies - Tatsuya Watanabe; Kosuke Nakamae; Junya Matsuda; Annora Dasi; Chihiro Miyagi; Syed Faizullah Hussaini; Satoshi Yuhara; Hirotsugu Kurobe; Daisuke Onohara; Toshiharu Shinoka (European Cells & Materials, 2026)
Tissue-engineered heart valves (TEHVs) have been developed to overcome the limitations of current prosthetic valves, which lack growth, repair, and remodeling capacity. While early TEHV strategies relied on pre-seeded cells, recent approaches have shifted toward cell-free scaffolds designed to promote in situ tissue regeneration; however, the relative advantages and limitations of these strategies remain unclear. This review synthesizes evidence from preclinical and clinical studies of TEHVs, including fully synthetic biodegradable scaffolds, decellularized xenografts, decellularized allografts, engineered decellularized matrices, and cell-seeded constructs, with a focus on scaffold composition, recellularization, extracellular matrix (ECM) formation, and functional durability. Overall, cell-free TEHVs demonstrate the ability to recruit host cells and support tissue formation, but remodeling is frequently incomplete and heterogeneous, particularly in valve leaflets. Decellularized xenografts show limited durability due to persistent immunogenicity, whereas decellularized allografts provide the most consistent clinical performance but exhibit incomplete recellularization and variable long-term outcomes. Fully synthetic and engineered decellularized scaffolds enable in situ regeneration but are often associated with geometric instability and maladaptive remodeling. Cell-seeded TEHVs can enhance early endothelialization and matrix deposition; however, challenges remain in cell retention, survival, and regulation of remodeling, with no consistent long-term superiority. Taken together, neither purely cell-free nor cell-seeded strategies alone reliably achieve durable valve regeneration, and the primary challenge lies in controlling remodeling rather than the presence of seeded cells, supporting the development of integrated approaches that combine scaffold design with biological modulation to improve long-term valve function.